Terrorism as a factor geopolitical restructuring in the Sahel region - Kante, Mady Ibrahim (Journal of Central and Eastern European African Studies, 2025)
Since the beginning of the new millennium, extremism has emerged as a major challenge facing the African continent. This phenomenon significantly impedes economic and political development, prompting individual states to fight terrorism through various initiatives. Despite these efforts, tangible results have been elusive due to the transfer of extremist ideologies across state borders, leading to external interventions under the guise of the “fight against terrorism in the Sahel.” Although jihadist terrorist groups have long been present in Africa, the Sahel countries and African organizations have not adopted effective strategies to combat violent extremism. Since 2011, terrorist organizations have seized control of areas in the Sahel, with Boko Haram conducting numerous operations that threaten regional security and stability. In response, African organizations such as the African Union and regional bodies have implemented policies and initiatives aimed at curbing the spread of violent extremism through military interventions and economic and social development projects in the Sahel. These efforts include alliances like the Lake Chad Basin Commission and G5 Sahel, comprising five Sahel countries. Given the regional and international ramifications of extremism on Western interests and economically powerful states, African nations and organizations have engaged in serious cooperation with the international community and major powers. This collaboration includes efforts with the United Nations, France, and other entities in peacekeeping missions and initiatives to combat terrorism and extremism. Keywords: Africa, Sahel, geopolitics, terrorism, war, counterterrorism, military intervention, security.